Philosophical aspect of installment trading in Islamic Rules - Assylbek, Sarsembayev (2021)
In this article, I would like to stop at one of the common types of trade called “Installment trading”, which is permitted in Islam, if the necessary conditions required in the Shari'ah will be fulfilled. At the same time, installment trading in Islam (Installment sale) is only one of many types of sale and purchase. Now this type of trade is very common in the world. Individuals and various industrial enterprises, firms, etc. use installment trading. Instalment selling is often used in Islamic financing. One of the types of installment trading is As-Salam, when payment for goods is made long before it was purchased, and which is known according to Arab sources long before Islam arose, used in Islam more than a thousand years ago. It should be noted that trade in Islam is permitted and this is because all the messengers of Allah were sent to change what God prohibited, but with regard to trade, there was no prohibition. In particular, the proof of that is the trade deals of the Messenger of Allah (peace be upon him).